Internet Addiction, Values, and Religiosity as Predictors of Life Satisfaction among Adolescents: A Quantitative Study on High School Students - AYTEN, ALİ (TURKISH GREEN CRESCENT SOC, 2019)
The main aim of this study is to examine the links among adolescents' religiosity; predisposition toward ethical values, Internet addiction, and life satisfaction levels. Furthermore, it also aims to determine whether the dependent variables (religiosity; ethical values, and Internet addiction) are predictors of life satisfaction among high school students. The participants of the study consist of 471 adolescents (236 males and 235 females) receiving their education in different high schools in Istanbul province during the 2017-2018 academic year. Research data have been collected using the survey method. A questionnaire form, the Religiosity Scale, Sensitivity to Ethical Values Scale, Young Internet Addiction Test- Short Form, and Life Satisfaction Scale have been used in addition to a demographic information form. The findings from the research indicate a positive correlation to exist among religiosity, ethical values, and life satisfaction and a negative correlation to exist among Internet addiction, ethical values, and life satisfaction. The findings additionally show ethical values, Internet addiction, and religiosity to be significant predictors of life satisfaction.
Keywords: Religiosity; Life satisfaction; Ethical values; Internet addiction; Young Internet Addiction Test; UNIVERSITY-STUDENTS; TERMS; GENDER